Alternative Approaches in Conflict Resolution
XXIII, 270 p. 6 illus., 2 illus. in color.
Keywords: “A gift to societies all over the world.” —Nico Koopman, Vice-rector for Social Impact, Transformation and Personnel, Stellenbosch University, South Africa. “This volume comes at the right time. … May this book inspire many to find new trust that a different world is possible!” —Heinrich Bedford-Strohm, Moderator of the WCC central committee “This superb volume … is to be welcomed by all scholars and practitioners.” —William Storrar, Center of Theological Inquiry in Princeton, USA In its second edition, this extended and revised volume brings together alternative and innovative approaches in conflict resolution. With traditional military intervention repeatedly contributing to instability and violence, the study of alternative approaches has become imperative. Can forgiveness help heal relationships in post-apartheid South Africa? How can art assist dealing with ‘unrememberable’ events such as the genocide in Rwanda? What transformational resources do women offer in contexts of massive human rights violations? The aim of this edited volume is twofold: to provide and encourage critical reflection of the approaches presented here and to explore concrete improvements in conflict resolution strategies. In its interdisciplinary and international outlook, this work combines the tried-and-tested approaches from conflict resolution experts in academia, NGOs and civil society, making it an invaluable tool for academics and practitioners alike. Christine Schliesser is Senior Lecturer at the Institute for Social Ethics at Zurich University and Director of studies at the Center for Faith and Society at Fribourg University, Switzerland. Martin Leiner is Chair of systematic theology and ethics at Jena University, Germany. .